Serum vitamin D deficiency in subjects with severe acquired brain injury and relationship with functional severity. (6th December 2018) - Intiso, D.; Fontana, A.; Copetti, M.; Di Rienzo, F.
ABSTRACT: Background : Vitamin D may be important for the development and function of the nervous system. Low serum vitamin D levels have been detected in several neurological diseases. Objective : To ascertain the relationship between 25(OH)D serum level and disability in subjects with severe acquired brain injury (sABI). Design : Prospective cross-sectional study Methods : Consecutive subjects with sABI admitted to neuro-rehabilitation were enrolled. A sample of subjects from the neurological ward was considered the control group. Vitamin D serum levels and blood parameters were measured at admission. Disability Rating Scale (DRS), Glasgow Outcome Scale (GOS), and Level of Cognitive Functioning (LCF) were used in assessing disability. Results : A total of 104 subjects (34 F, 70 M; mean age 53.9 ± 15.2 years) were enrolled: 54 (19 F, 35 M) with sABI and 50 (15 F, 35 M) subjects as control group. Deficient mean serum levels of vitamin D (19.2 ± 9.4 ng/mL) were detected in the subjects with sABI and a significant inverse correlation between vitamin D serum levels and DRS score was detected (p = 0.04). Conclusion : Subjects with sABI showed vitamin D deficiency that might correlate to disability severity. The reason is unclear and might represent a secondary phenomenon resulting from the inflammatory process.